Covid-19 in pregnancy woman and perinatal outcomes at the Hospital Materno Infantil El Carmen - Huancayo - 2022 - Solano Tacza , Jim Kelvin (2023)
Objective: To identify the perinatal outcomes in pregnant women who were diagnosed with COVID-19 who attended the Hospital Materno Infantil El Carmen - Huancayo from January to March of the year 2022.  Material and Methods: It is an observational, retrospective, cross-sectional investigation, developed with 66 pregnant women diagnosed with COVID-19 attended in the first quarter of a year. Results: Of the 66 pregnant women with COVID-19, 10.65% are 29 years old, 86.4% come from an urban area, while 84.8% have as their occupation being a housewife. The total population presented mild COVID-19. Regarding deliveries: postterm 16.7%, preterm 10.6% and term 72.7%. Vaginal deliveries registered 33.3%, upper route 66.7%, pregnancy-induced hypertension was the infrequent pathology (3.03%). The diagnosis referring to anthropometric measurements obtains that the weight for gestational age is adequate in 89.4% while weight for gestational age is inadequate in 10.6%, during childbirth light green amniotic fluid was found in 1% and meconium fluid 0%. In newborns, the highest proportion presented Apgar 7 to 10 at one minute in 95.5% and at 5 minutes in 100%, a newborn was found with a positive result for COVID-19. Conclusions: Neonates of pregnant women with mild COVID-19 are small for their gestational age, which leads us to presume compromised fetal growth, a positive COVID-19 test was had.